Is live-tissue training ethically justified?: an evidence-based ethical analysis - Rubeis, Giovanni; Steger, Florian (Alternatives to laboratory animals, 2018)
Trauma training is a crucial element of medical education in the civilian sector, as well as in the military sector. Its aim is to prepare physicians, medics and nurses for stressful and demanding emergency situations. Training methods include live-tissue training (LTT) on animal models and simulation-based trauma education. For LTT, blast, gunshot or stab wounds are inflicted on anaesthetised animals, mostly goats and pigs, but sometimes non-human primates. This training method raises ethical concerns, especially in the light of increasingly sophisticated simulation-based methods. Despite these non-animal alternatives, LTT is still widely used due to its presumed educational benefits. In this paper, the question of whether LTT can still be justified, is discussed. We developed a normative framework based on the premise that LTT can only be ethically justified when it yields indispensable benefits, and when these benefits outweigh those of alternative training methods. A close examination of the evidence base for the presumed advantages of LTT showed that it is not superior to simulation-based methods in terms of educational benefit. Since credible alternatives that do not cause harm to animals are available, we conclude that LTT on animal models is ethically unjustified.
Gesehen am 12.05.2021